2006
DOI: 10.1001/archinte.166.12.1289
|View full text |Cite
|
Sign up to set email alerts
|

Reemergence of Gram-negative Health Care–Associated Bloodstream Infections

Abstract: To our knowledge, this is the first US study to report a reemergence of gram-negative organisms as a cause of PHA-BSIs. This finding does not seem to be related to changes in specific gram-negative organisms or to antimicrobial resistance. If this trend continues, it will have important implications for the management of bloodstream infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 39 publications
(43 reference statements)
6
49
0
Order By: Relevance
“…Therefore, changes in our demographics do not appear to be the primary driver of this pathogenic shift. Similar trends in rates of fungal infection have been demonstrated elsewhere, although the most common Candida species differs by institution [13,[15][16][17][18]. One study found blood transfusion to be an independent risk factor for non-Candida albicans fungemia [19].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, changes in our demographics do not appear to be the primary driver of this pathogenic shift. Similar trends in rates of fungal infection have been demonstrated elsewhere, although the most common Candida species differs by institution [13,[15][16][17][18]. One study found blood transfusion to be an independent risk factor for non-Candida albicans fungemia [19].…”
Section: Discussionsupporting
confidence: 67%
“…Albrecht et al reported a similar increase in gram-negative BSI, which was correlated with greater hospital-wide utilization of levofloxacin. However, our fluoroquinolone utilization remained stable over the study period [13]. Further study will be required to evaluate what impact, if any, shifting trends in antimicrobial utilization have on the spectrum of BSI pathogens in our institution.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, the reemergence of Gram-negative organisms as a cause of primary BSIs has also been reported (1). In the United States, Escherichia coli is the fifth most common cause of nosocomial BSIs and is the first most common cause among Gram-negative organisms, and BSIs caused by E. coli are reported to be associated with a crude mortality rate of 22% (34); in Spain, it is the second most common cause of nosocomial BSIs (23).…”
mentioning
confidence: 99%
“…Therefore, our results are not necessarily applicable to other settings and populations. However, the bloodstream isolates we encountered are representative of those commonly reported in Italian hospitals and in other parts of the world as well (52,53). Almost half (47.9%) of the microorganisms responsible for our patients' BSIs were Gram-negative bacilli, many of which were multidrug-resistant (data not shown).…”
Section: Discussionmentioning
confidence: 66%